Proceedings of the 28th ACM Symposium on Virtual Reality Software and Technology 2022
DOI: 10.1145/3562939.3565630
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User Behaviour in Asymmetric Collaborative Mixed Reality

Abstract: Figure 1: Conceptual overview of our collaborative MR system, in which an AR and a VR user can collaborate remotely. The CVE contains a static 3D model of Space B. Users are represented with avatars. Line illustrations by Suhyun Park (artist).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Our prototype system is built using the open-source social VR framework Ubiq [9] (Unity version 2020.3.40f1) and is based on an existing implementation of an asymmetric CMR system [25]. Our system supports collaboration between a local outdoor AR user and remote VR users.…”
Section: Outdoor Cmr Systemmentioning
confidence: 99%
“…Our prototype system is built using the open-source social VR framework Ubiq [9] (Unity version 2020.3.40f1) and is based on an existing implementation of an asymmetric CMR system [25]. Our system supports collaboration between a local outdoor AR user and remote VR users.…”
Section: Outdoor Cmr Systemmentioning
confidence: 99%
“…Real-time metrics could be included to inform researchers about the level of user activity (e.g. head rotation velocity and words spoken [17]), communication style (e.g., recognition of F-formations [22]), emotional state (e.g., sentiment analysis using natural-language processing [7]), and user experience (e.g. the objective representations of presence and co-presence [18]).…”
Section: Services and Applicationsmentioning
confidence: 99%
“…As past studies have shown, such AR experiences can effectively engage users and facilitate collaboration in architectural contexts [22]. Building on the proven potential of MR collaboration [17], our project integrates AR-driven user engagement with collaboration among VR and AR users.…”
Section: Reviving Culture Heritage: the Euston Archmentioning
confidence: 99%
“…We are particularly focused on integrating photo-realistic world models into AR/VR experiences to foster seamless collaboration between AR and VR users. Building on our previous research in indoor environments [17] and standalone models of outdoor scenes [16], we explore diverse collaboration possibilities between AR and VR users within outdoor settings, using world models and accurate tracking. Moreover, we strive to enhance communication and interaction methods that could facilitate a fluid transition across the reality-virtuality continuum [15].…”
Section: Introductionmentioning
confidence: 99%